Non-governmental Organisations : their Role in Forestry Research and Extension - Varalakshmi, V.; Kaul, O. N. (Indian Forester, 1999)
The priority areas of concern call for reorientation of forest management policies and development programmes in the context of environmental security and maintenance of biological diversity. What is increasingly evident is the need to expand the forest resources base and productivity, besides effective involvement and participation of local communities in establishing sustainable forest management systems. NGOs have essentially been playing the role of a facilitator in bridging the gap between forest dependent communities and the Forest Departments catering so far primarily to sociological aspects of development projects. Forestry research will essentially require relevant government agencies, Universities, NGOs and grassroot organisations to collaborate on action research, training and information sharing activities. A good networking of organisations coupled with effective extension mechanisms would be a successful combination. Constraints to effective NGO involvement in forestry development programmes stem from misunderstanding of NGO strengths and weaknesses, contractual and funding hurdles such as finding a way to channel funds to NGOs in advance, mutual distrust, and the lack offin many cases non-recognition of managerial and technical skills among many NGOs. Special programmes are needed to strengthen NGOs to enable them to play a greater supporting role in the Forestry sector. For NGOs to play an effective and meaningful role, coordination and collaboration for forestry research and extension could be at various levels from the grassroots to the policy making level.